2019
DOI: 10.3390/pr7100705
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Conversion of Napier Grass for Production of Renewable Syngas

Abstract: Fuel resource diversification is a global effort to deviate from non-renewable fossil fuels. Biomass has been identified as an alternative solid biofuel source due to its desirable properties and carbon neutrality. As reported in the literature, biomass can positively contribute towards combating climate change while providing alleviation for energy security issue. As part of efforts to diversify biomass resources, this work intends to explore the potential of Napier grass, one type of energy crop, for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Moisture content was similar at 30, 60, and 90 d (p > 0.05; Table 1) and difference was only observed at 120 d (p ≤ 0.05), which showed the lowest moisture content. The calorific value in the present experiment ranged from 14.9 to 15.1 MJ kg -1 , which was lower than that reported by Said et al (2019) who found 16.7 MJ kg -1 in Napier grass (C. purpureus). Likewise, Karampinis et al (2012) reported 18.7 MJ kg -1 in miscanthus (Miscanthus giganteus).…”
Section: Calorific Value and Moisture Contentcontrasting
confidence: 89%
“…Moisture content was similar at 30, 60, and 90 d (p > 0.05; Table 1) and difference was only observed at 120 d (p ≤ 0.05), which showed the lowest moisture content. The calorific value in the present experiment ranged from 14.9 to 15.1 MJ kg -1 , which was lower than that reported by Said et al (2019) who found 16.7 MJ kg -1 in Napier grass (C. purpureus). Likewise, Karampinis et al (2012) reported 18.7 MJ kg -1 in miscanthus (Miscanthus giganteus).…”
Section: Calorific Value and Moisture Contentcontrasting
confidence: 89%
“…In this work, the pyrolysis reaction scheme, as shown in Equation (1), was proposed as the decomposition of biomass, producing solid char, liquid products (H 2 where x, y and z are mole ratios of carbon, hydrogen and oxygen which give the chemical formula for the biomass and their values are listed in Table 1 for various biomass precursors used in the present study. Symbols a to q represent the stoichiometric numbers of the products produced from the pyrolysis process.…”
Section: Simulation Of the Pyrolysis Processmentioning
confidence: 99%
“…Symbols a to q represent the stoichiometric numbers of the products produced from the pyrolysis process. The rate of biomass decomposition is assumed to follow the first-order rate expression, as shown in Equation (2).…”
Section: Simulation Of the Pyrolysis Processmentioning
confidence: 99%
See 2 more Smart Citations